2015
DOI: 10.1371/journal.pone.0131417
|View full text |Cite
|
Sign up to set email alerts
|

Truncating Homozygous Mutation of Carboxypeptidase E (CPE) in a Morbidly Obese Female with Type 2 Diabetes Mellitus, Intellectual Disability and Hypogonadotrophic Hypogonadism

Abstract: Carboxypeptidase E is a peptide processing enzyme, involved in cleaving numerous peptide precursors, including neuropeptides and hormones involved in appetite control and glucose metabolism. Exome sequencing of a morbidly obese female from a consanguineous family revealed homozygosity for a truncating mutation of the CPE gene (c.76_98del; p.E26RfsX68). Analysis detected no CPE expression in whole blood-derived RNA from the proband, consistent with nonsense-mediated decay. The morbid obesity, intellectual disab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 44 publications
0
55
0
Order By: Relevance
“…This could result in a higher diagnostic yield than the definite molecular diagnosis of 3.9% that we present here with NGS gene panel testing. Since research in obesity genetics is rapidly progressing, recently identified obesity-associated genes, such as CPE were not included in this panel 26. These genes can be added to the next version of our diagnostic obesity gene panel.…”
Section: Discussionmentioning
confidence: 99%
“…This could result in a higher diagnostic yield than the definite molecular diagnosis of 3.9% that we present here with NGS gene panel testing. Since research in obesity genetics is rapidly progressing, recently identified obesity-associated genes, such as CPE were not included in this panel 26. These genes can be added to the next version of our diagnostic obesity gene panel.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, mutation in the CPE gene has been found in the brain from a patient with Alzheimer’ disease[10]. Furthermore, a person who bears homozygosity for a truncating mutation of the CPE gene displayed intellectual disability[19]. The hypothesis that CPE mutation would contribute to neurological disorders is also supported by the animal studies showing that CPE-KO mice had the neuronal loss of the CA3 region of hippocampus, displayed memory deficits and depressive-like behaviors[12,13,20].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study showed that a truncating mutation of the CPE gene found in a female from a consanguineous family, led to morbid obesity, intellectual disability, hypogonadotrophic hypogonadism and abnormal glucose homeostasis[19]. Additionally, a number of mutations in the human CPE gene have been reported and some are associated with endocrine problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In genomewide association studies (GWASs), the strongest genetic signal for body mass index is located in the FTO locus, wherein polymorphic differences in noncoding nucleotide sequences may change the basic function of human adipocytes from energy storage to energy utilization via enhanced thermogenesis 13,14 . Furthermore, monogenic diseases that cause severe cases of obesity are described and include leptin and leptin receptor deficiency, SH2B1 mutations, and carboxypeptidase E mutations [15][16][17] . Table 3 lists illustrative genetic obesity syndromes experienced by patients, and managed by clinicians, along with their genetic abnormalities [16][17][18][19][20][21][22][23][24] .…”
Section: Pathogenic Potential Of Adipose Tissuementioning
confidence: 99%